Social loafing among learner support staff for open and distance education programmes in south-western Nigeria: the imperative for counselling intervention. (2nd January 2022) - Ofole, Ndidi Mercy
ABSTRACT: A descriptive survey design was adopted to investigate the relationship that exists amongst locus of control, work engagement, organisational reward system, job satisfaction and social loafing among the staff of distance learning programme in South-western Nigeria. Four hundred and forty-seven (males = 184; females = 263) learners support staff with an age range of 22 to 55 years were randomly drawn from open and distance learning universities located in South-western Nigeria. They responded to five standardised self-report questionnaires. The results show that the majority (67.6%) of the respondents reported different forms of social loafing. There was a significant gender difference in the social loafing behaviour scores of male and female [t (445) = 0.773, p < 0.01]. Male respondents reported more social loafing behaviour (x? = 40.95) than their female counterparts (x = 25.48). There was a positive relationship between locus of control and social loafing though not significant. The relationship among job satisfaction, work engagements as well as reward system and social loafing were inverse. It concluded that personal and organisational factors predispose workers to social loafing. It is recommended that ODL management should also put in place better systems of reward practice and recognition. Counselling intervention is also required to reorient learner support staff who are loafers at OD institutions.